Analysis of Muslim Students' Consumption Behavior Based on an Islamic Economic Perspective - Ana Fitrotun Nisa’; Achmad Budi Susetyo (Penerbit Hellow Pustaka, 2026)
This study aims to analyze the consumption behavior of Muslim university students from the perspective of Islamic economics, with a focus on how core sharia principles such as halal consumption, balance (wasathiyah), and the avoidance of extravagance (israf) are implemented in their daily lives. In today's academic environment, student consumption patterns have shifted from being needs-based to being heavily influenced by lifestyle trends and external pressures, including social media and peer expectations. This shift presents a significant challenge in aligning real-life consumption practices with Islamic ethical values. Using a qualitative approach, this research collects data through in-depth interviews with Muslim students from diverse economic backgrounds. The analysis explores how students perceive and interpret Islamic economic principles and how these values influence (or fail to influence) their consumption decisions. The findings reveal that although many students possess a basic understanding of Islamic consumption ethics, their actual behavior is still shaped by consumerist culture, limited sharia economic literacy, and socio-economic pressures. Self-control and financial awareness are often compromised, especially in the face of modern-day temptations and inadequate institutional guidance. Therefore, the study recommends strengthening Islamic economic education in a more practical and contextual manner within university settings. Such education should not only enhance theoretical understanding but also encourage ethical and responsible decision-making in financial and consumption matters. By integrating Islamic values into everyday economic choices, students can become not only academically capable but also morally grounded individuals in navigating the challenges of modern consumer culture